Safety and Efficacy of Nebulised Anti-Inflammatory Solution of Alkaline Hypertonic Ibuprofen (AHI) for Treatment of SARS-Cov-2 Infection: A Compassionate Study with a Comparator Arms. Issue 2 (2022) - Kalayan, Galia, Martinez Rios, Ana Carolina Arias Cau, Luis Argarañas; García, Néstor
No abstract available